2017
DOI: 10.1021/acs.jproteome.6b00984
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Modulation Attenuated the Hypolipidemic Effect of Simvastatin in High-Fat/Cholesterol-Diet Fed Mice

Abstract: Interindividual differences in hypolipidemic effect of simvastatin are observed in clinic, and metabolomic studies have uncovered the association between variations of bacterial-derived metabolites and therapeutic outcomes. In current study, we investigated the gut microbial-involved mechanisms underlying the different responses to simvastatin. Male C57BL/6J mice were given high-fat/cholesterol diet (HFD) 8 weeks and then orally administered simvastatin (20 mg/kg, once a day) for 4 weeks with or without antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 39 publications
(95 reference statements)
6
33
0
Order By: Relevance
“…This modulation of the gut microbiota via antibiotics further impacted the expression of serum metabolites such as phospholipids, bile acids, and hepatic cholesterol 7 alpha‐hydroxylase genes ( CYP7A1 , CYP7B1 ). These hepatic genes also regulate the bile acid biosynthesis from cholesterol . Therefore, in summary, He et al .…”
Section: The Indirect Impact Of Gut Microbiota In Drug Response and Tmentioning
confidence: 97%
See 1 more Smart Citation
“…This modulation of the gut microbiota via antibiotics further impacted the expression of serum metabolites such as phospholipids, bile acids, and hepatic cholesterol 7 alpha‐hydroxylase genes ( CYP7A1 , CYP7B1 ). These hepatic genes also regulate the bile acid biosynthesis from cholesterol . Therefore, in summary, He et al .…”
Section: The Indirect Impact Of Gut Microbiota In Drug Response and Tmentioning
confidence: 97%
“…Positive correlations have been observed between plasma concentrations of simvastatin and bacterial‐derived primary and secondary bile acids, especially in good responders . He et al ., in 2017, using a metabolomics survey, demonstrated that simvastatin reduced the levels of serum total cholesterol, low‐density lipoprotein, high‐density lipoprotein, and triglyceride in mice fed with high‐fat diet, which, however, could be attenuated by antibiotic treatment that in turn modulated the composition of gut microbiota . This modulation of the gut microbiota via antibiotics further impacted the expression of serum metabolites such as phospholipids, bile acids, and hepatic cholesterol 7 alpha‐hydroxylase genes ( CYP7A1 , CYP7B1 ).…”
Section: The Indirect Impact Of Gut Microbiota In Drug Response and Tmentioning
confidence: 99%
“…Only a few studies have shown the impact of the microbiota on statin efficacy. Still, these studies suggested that the microbiota participated in statin's effect (He et al, 2017) and was responsible for statin metabolization (Yoo et al, 2014) and that the microbiota from patients unresponsive to statin was different from that of responsive patients (Sun et al, 2018).…”
Section: Impact Of the Microbiota On Hypocholesterolemic Drug Efficacymentioning
confidence: 99%
“…It has been reported that gut microbiota play roles in the mediation of lovastatin metabolism and consequent pharmacokinetics interactions [15]. The hypolipidemic effects of SIM [16], ROS [17], and ATO [18] were shown to be correlated with the compositions of mice gut microbiota. Statins have certain antibacterial functions and have been described as novel adjuvant antibiotics [10], but we know little about the statin effects on the human gut bacterial microbiota.…”
Section: Introductionmentioning
confidence: 97%